The EFFECT OF INFLUENCER MARKETING AND TIKTOK CONTENT STRATEGIES ON PURCHASING DECISIONS WITH TRUST AS A MEDIATING VARIABLE IN ELFORMULA SKINCARE PRODUCTS Case Study of Jambi University Students - Maharani; Yacob, Syahmardi; Fitriaty (Journal of Business Studies and Management Review, 2026)
This study aims to analyse the influence of influencer marketing and TikTok content strategy on purchasing decisions for Elformula skincare products, with trust as a mediating variable. Using a quantitative approach, data was collected from 118 respondents through a questionnaire designed using a Likert scale. The analysis method involved multiple linear regression and mediation test. The results showed that influencer marketing and TikTok content strategy significantly influenced trust and purchase decision. Furthermore, trust was shown to partially mediate the influence of influencer marketing on purchase decisions, as well as partially mediate the influence of TikTok content strategy on purchase decisions. These findings confirm the importance of brands' collaboration with credible influencers and development of authentic and engaging content strategies on TikTok, not only to drive direct purchases but also to build and maintain consumer trust. This research provides important insights for brands in optimising their digital marketing strategies in the competitive skincare market.